2017
DOI: 10.4238/gmr16019195
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of invasion and migration of prostate cancer cells by miRNA-509-5p via targeting MDM2

Abstract: ABSTRACT. Prostate cancer is a common malignancy of the male reproductive-urinary system. MDM2 is an oncogene, whose expression can be regulated by microRNA (miRNA). The present study investigated the expression and correlation of miRNA-509-5p and MDM2 to determine the mechanism of their function in invasion and migration of prostate cancer cells. RT-PCR was performed to detect the expression of miRNA-509-5p and MDM2 in tumor, tumor-adjacent, and normal tissues, obtained from prostate cancer patients, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The important function of MDM2-p53 axis in the development of cancer led to the discovery of potential anti-cancer approaches that disrupted the interaction of p53 with MDM2 or targeted MDM2. Notably, MDM2 was also identified as the targets of miRNAs that modulated the growth of cancer cells 25,26. For example, recent study showed that miR-758-3p suppressed the proliferation, migration and invasion of hepatocellular carcinoma cells by targeting MDM2 27.…”
Section: Introductionmentioning
confidence: 99%
“…The important function of MDM2-p53 axis in the development of cancer led to the discovery of potential anti-cancer approaches that disrupted the interaction of p53 with MDM2 or targeted MDM2. Notably, MDM2 was also identified as the targets of miRNAs that modulated the growth of cancer cells 25,26. For example, recent study showed that miR-758-3p suppressed the proliferation, migration and invasion of hepatocellular carcinoma cells by targeting MDM2 27.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the downregulated expression of miRNA may be essential in the onset and development of PCa ( 21 – 23 ). In addition, increased expressed of miRNA was likely to regulate the expression of target genes and exert its influences on the progression of PCa ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, upregulation MDM2 has been detected in non-small cell lung cancer, gastric cancer and bladder cancer, acting as a sponge of miR-1305, miR-410 and miR-379-5p, respectively ( 36 38 ). Additionally, the 3′-UTR of MDM interacts with miRNA-509-5p and miR-129 to modulate the progression of prostate cancer and glioma ( 39 , 40 ). The data from the present study confirmed that MDM2 was upregulated in PC tissues and the 3′-UTR of MDM2 is a direct target of miR-2113.…”
Section: Discussionmentioning
confidence: 99%